The memory altar - Alexander-McKenna, Hilary Jane (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a novella that casts a sideways glance at the real world that at times seems stranger than fiction. The novella is written as a work of realistic fiction, with a plot, characters, timelines and location placed in present time, reflecting real current events. My work is strongly influenced by writers such as Ivan Vladislavić whose Portrait with Keys uses a slice of life narrative voice that observes overlays of public and private realities; Marguerite Duras' use of cinematic storytelling and deeply personal exposure in The Lover and Yann Andréa Steiner; Kate Zambreno's depiction of inner chaos against the chaos of an anonymous city in Green Girl; Otessa Moshfegh who makes the minutiae of the day-to-day seem significant in My Year of Rest and Relaxation; and Samuel Beckett's finely crafted streams of consciousness, in his works of prose and drama, revealing the intimate perspectives of insiders.
Keywords: Creative writing (Higher education) -- South Africa; Diaries -- Authorship; South African fiction (English) 21st century; South African essays (English) 21st century; South African essays (English) History and criticism; South African fiction (English) History and criticism; Yuknavitch, Lidia Criticism and interpretation; American fiction Criticism and interpretation; COVID-19 (Disease) in literature